2023
DOI: 10.1177/00018392231212680
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Partner Organizational Structure on Innovation

Sarath Balachandran,
John Eklund

Abstract: Interorganizational partnerships can spur innovation, but their value may be diminished by friction in knowledge flows between firms. We consider how a partner’s organizational structure may influence the knowledge that is accessible via partnerships. We focus on how a partner’s structure trades off localized autonomy for its managers, which facilitates timelier decision making, and unified control, which facilitates integration. By shaping this balance, centralization of decision rights within the partner org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…This study documents the role such experience can play in enabling startups to navigate external partnerships, which can often be critical to these firms' outcomes (Katila et al, 2021). More broadly, the findings highlight the importance of intrafirm factors in shaping the exchanges and outcomes arising in interfirm relationships, which have received limited attention in prior work (Balachandran & Eklund, 2023).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…This study documents the role such experience can play in enabling startups to navigate external partnerships, which can often be critical to these firms' outcomes (Katila et al, 2021). More broadly, the findings highlight the importance of intrafirm factors in shaping the exchanges and outcomes arising in interfirm relationships, which have received limited attention in prior work (Balachandran & Eklund, 2023).…”
Section: Introductionmentioning
confidence: 71%
“…Despite these and other limitations, this study represents a meaningful addition to recent work highlighting the importance of intrafirm factors in shaping the exchanges that arise in interfirm relationships (e.g., Balachandran & Eklund, 2023). Classic approaches to examining interfirm relationships adopt monolithic views of firms to examine how their aggregate characteristics, such as their resources and capabilities, affect the formation and performance of interfirm ties.…”
Section: Discussionmentioning
confidence: 98%
“…The social, economic and sustainability benefits of powerful and emerging communications technologies have been shown to vary according to geography and regional culture [49,50], and it has also been shown that smart services have higher rates of adoption when aligned to cultural preferences [29,30]. This stresses the point, already made, that smart sustainable city planners and strategists should prioritise the selection and adaption of culturally aligned technologies, if they are to maximise public acceptance and societal benefit [51,52]. It therefore follows that the potential of smart sustainable city implementation is best understood through the study and analysis of specific urban regions [49,53].…”
Section: Literature Reviewmentioning
confidence: 99%